Non‐Equilibrium Synthesis of Highly Active Nanostructured, Oxygen‐Incorporated Amorphous Molybdenum Sulfide HER Electrocatalyst. Issue 44 (8th October 2020) - Giuffredi, Giorgio; Mezzetti, Alessandro; Perego, Andrea; Mazzolini, Piero; Prato, Mirko; Fumagalli, Francesco; Lin, Yu‐Chuan; Liu, Chenze; Ivanov, Ilia N.; Belianinov, Alex; Colombo, Massimo; Divitini, Giorgio; et al.
Abstract: Molybdenum sulfide emerged as promising hydrogen evolution reaction (HER) electrocatalyst thanks to its high intrinsic activity, however its limited active sites exposure and low conductivity hamper its performance. To address these drawbacks, the non‐equilibrium nature of pulsed laser deposition (PLD) is exploited to synthesize self‐supported hierarchical nanoarchitectures by gas phase nucleation and sequential attachment of defective molybdenum sulfide clusters. The physics of the process are studied by in situ diagnostics and correlated to the properties of the resulting electrocatalyst. The as‐synthesized architectures have a disordered nanocrystalline structure, with nanodomains of bent, defective S‐Mo‐S layers embedded in an amorphous matrix, with excess sulfur and segregated molybdenum particles. Oxygen incorporation in this structure fosters the creation of amorphous oxide/oxysulfide nanophases with high electrical conductivity, enabling fast electron transfer to the active sites. The combined effect of the nanocrystalline pristine structure and the surface oxidation enhances the performance leading to small overpotentials, very fast kinetics (35.1 mV dec −1 Tafel slope) and remarkable long‐term stability for continuous operation up to ‐1 A cm −2 . This work shows possible new avenues in catalytic design arising from a non‐equilibrium technique as PLD and the importance of structural and chemical control to improve the HER performance of MoS‐based catalysts. Abstract : Hierarchical nanostructures with tunable mesoscale morphology are grown by the sequential attachment of defective molybdenum disulfide nanoparticles thanks to the non‐equilibrium characteristics of pulsed laser deposition. The disordered nanoscale organization of the material and the incorporation of oxygen to form conductive surface phases enables fast hydrogen evolution reaction electrocatalysis and prolonged stability at high applied current density.